Low-Level Laser Therapy: “Western School” vs “Eastern School” - Moskvin, Sergey (Journal of Lasers in Medical Sciences, 2021)
This article is in Editorial form and doesn't need the abstract. DOI: 10.34172/jlms.2021.66.